Sport and religion in the twenty-first century - Schultz, Brad, 1961-; Sheffer, Mary Lou. (Lanham, Maryland : Lexington Books, 2016)
This book examines the relationship between sport and religion with regard to twenty-first century topics such as race, fandom, education, and culture. The contributors provide new insights into the people, movements, and events that define the complex relationship between sport and religion around the world.
Who's Got Game? America's New Religion / Mary Lou Sheffer -- From Sunday Sermon to Monday Night Football: The Rise of the Use of Prayer in North American Sports / Alan Goldenbach -- Elegy for the McPheean Moment: False Idols and the Tyrannical Faith of Celebrity-Sports Culture / Jeffrey B. Kurtz -- Biblical Tales in the Sports News: Narrative and the Redemption of Michael Vick / Chris B. Geyerman -- An Olympic Religion: Does the IOC Still Have Faith in the Olympic Games? / Anthony J. Moretti -- "Be Not Conformed": The Relationship Between Modern Sport and Religion / Brad Schultz -- A Useable Soccer Martyr: The Egyptian Ultras and their Fight for Legitimacy / Natalia Mielczarek -- Celebrating in a Cemetery: Sport, the Sacred, and a Search for Significance in Fan Communities / Bruce J. Evensen -- Southern Reconstructing: Sport and the Future of Religion in the American South / Eric Bain-Selbo and Terry Shoemaker -- Exercising the Spiritual Muscle: Holistic Care Service Provision in Intercollegiate Athletics / Landon T. Huffman, Robin Hardin, and Steven N. Waller -- Are Sports Programs at Small Church-Affiliated Colleges and Universities Really Different? / Patrick J. Sutherland -- "Our Hope is Built on Nothing Less": Why Religion-Spirituality Matters in the Lives of Black Male College Athletes / Steven N. Waller.
Includes bibliographical references and index.
Keywords: Sports -- Religious aspects